Modern authoritarian regime: characteristics and manifestations - Skrypniuk, Oleksandr (ScienceRise: Juridical Science, 2020)
The article examines the modern authoritarian regime, considers its characteristics and manifestations. The author gives an overview of modern authoritarian regimes. The purpose of this article is to determine the nature and features of the authoritarian regime, as a kind of political regime, as well as the reasons that lead to its emergence or maintenance in the country. It is noted, that the authoritarian regime is not an evolutionary form of state development, it is always a logical consequence of the socio-political processes taking place in the country. It is noted, that it appears against the background of breakthrough processes, when the political system of the state needs changes, but these changes occur under the influence of the political elite, not society, which in turn allows us to identify the preconditions for an authoritarian regime in the state. It is stated, that the authoritarian regime is not an evolutionary form of state development, it does not provide high-quality succession of power, it is unable to offer new trends and transformations of public life due to the inability of one person to change their worldview, adapting to social demands and processes. It is noted, that most authoritarian countries do not proclaim, do not identify themselves in this way, but on the contrary try to position themselves as countries that promote democratic values. Authoritarian regime as such is not perceived by most countries in the world, as it is characterized by unstable, non-transparent and unpredictable development of socio-economic and socio-political processes. The dominance of liberal democracy in the tradition of economic relations demonstrates the tendency of socio-political preferences of most business elites to operate in the conditions of projected democratic regimes. It is concluded, that the authoritarian regime is based on the imperative planting of those values that will contribute to the maintenance of power, and therefore dominated by state ideology, which is planted by the forces and means of state propaganda. Citizens are deprived not only of real influence on the formation of state policy, but also of tools for supervision and control over the activities of the state apparatus